Archaeological theory in the new millennium : introducing current perspectives - Harris, Oliver J.T
Provides an accessible account of the changing world of archaeological theory. It charts the emergence of the new emphasis on relations as well as engaging with current theoretical trends and the thinkers archaeologists regularly employ. This book will be an essential guide to cutting-edge theory for students and for professionals wishing to reacquaint themselves with this field. Oliver J.T. Harris is lecturer in archaeology in the School of Archaeology & Ancient History, University of Leicester. Craig N. Cipolla is lecturer in historical archaeology in the School of Archaeology & Ancient History, University of Leicester.